O texto teatral em sala de aula: teoria e prática - Farias, Maria Normélia de (2021)
Training literary readers in a society that increasingly demands creativity, autonomy, speed, criticality and learning in several areas of knowledge become urgent for the integral formation. Aiming to collaborate for the improvement of the teaching-learning process in Portuguese language in elementary education, on this literary literacy journey, this work defends the importance of the studying the theatrical text and their compositional elements in the classroom through expressive readings, for the proficient readers formation, associating theory with practice. Studying the characteristics and functions of the compositional elements of the theatrical text will be a dynamic of “learning by doing” and, therefore, motivating the student’s practice of Reading, interpreting, making inferences with greater security and in a pleasant way. In order to developing literary readings, the work Coeteris paribus, by the playwright from Sergipe Cícero Alberto (1983), will be worked on. The methodology was the qualitative nature and this is founded into the reflections from Candido (2004), Compagnon (2009), Todorov (2009), Rosenfeld (2004); in the theories of reading by Lajolo (2009), Marcuschi (2008), Koch (2015), Ferrarezi (2017); in the theatrical theories of Betti (2002), Ryngaert (1996) and Vidor (2016). With the information collected in the development of the intervention this work, a Pedagogical Planning will be prepared where all the steps are registrated into the theatrical text studies, in order to contribute to the autonomous formation, critical and reflective readers, as proposed by the Common National Base Curricular (BRASIL, 2018), the National Curriculum Parameters, 1998) and the State of Sergipe Curriculum Framework (SERGIPE, 2018).